O regime de colaboração e os sistemas de ensino: um mapeamento de experiências em Belém do Pará - SILVA, Marina Martins da (2020)
The federal organization of the Brazilian state in collaboration established by the Federal Constitution of 1988 revealed the importance of giving attention to the processes that permeate intergovernmental relations for the scope of basic education in Brazil, specifically for the construction of its education systems. This paper aim to present a survey of projects, programs developed in the Municipal Education Department of Belém, from 2014 to 2018 that may indicate the promotion of the collaboration regime. For this, It is possible to contemplate a democratic and effective management by means of the collaboration system, since this contributes to the positive development of the relations between the federated entities, motivating a work of promising bases for the improvement of the advancement of education. In spite of this, some challenges to its execution were identified, among which the lack of regulation stands out, being the search for work based on the federative balance, the municipalization and the promotion of values such as cooperation and participation are shown as the main solutions to the problems identified from the study. Given the relevance of the collaboration regime for the effectiveness of democratic management in the educational field, a mapping of the experiences of the collaboration regime in Belém was carried out to analyze its development and materialization at the local level.